DEHUMIDIFIER USING GEOTHERMAL HEAT - OKAUCHI YOSHITOMO; TAKAI MAKOTO (2016)
PROBLEM TO BE SOLVED: To solve the problem in which, when humid air during a rainy season and a summer season is taken in the indoors, people feel uncomfortable, and energy is wasted when an air conditioning machine such as a dehumidifier and an air conditioner is used to solve the problem.SOLUTION: Humid air during a rainy season and a summer season is taken in by using a pipe instead of taking in directly indoors, and the air is supplied to the indoors via the pipe embedded underground. The air taken in from outdoors reaches a dew point and condenses dew in the pipe embedded underground. The air itself is dehumidified. By supplying the air dehumidified in the pipe embedded underground to the indoors, discomfort can be alleviated. Only small energy consumption is necessary for power, so that this contributes to energy saving.SELECTED DRAWING: Figure 1 【課題】梅雨時期や夏場の湿潤な空気を屋内に取り込むことにより、人は不快に感じる。これを解決するために除湿器やエアコンなどの空調機を使うことでエネルギーの無駄遣いが発生する。【解決手段】梅雨時期や夏場の湿潤な空気を屋内に直接取り込まずに、管を用いて取り込み、地中に埋設した管を経由してから屋内に空気を供給する。地中に埋設した管の中で屋外から取り込まれた空気は露点に達して結露をする。空気そのものは除湿される。地中に埋設した管内部で除湿された空気を屋内に供給することで、不快感を軽減する。動力は小さなエネルギー消費で済むため省エネルギーに貢献するものとなる。【選択図】図１